8t+6=6+7t

Simple and best practice solution for 8t+6=6+7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t+6=6+7t equation:


Simplifying
8t + 6 = 6 + 7t

Reorder the terms:
6 + 8t = 6 + 7t

Add '-6' to each side of the equation.
6 + -6 + 8t = 6 + -6 + 7t

Combine like terms: 6 + -6 = 0
0 + 8t = 6 + -6 + 7t
8t = 6 + -6 + 7t

Combine like terms: 6 + -6 = 0
8t = 0 + 7t
8t = 7t

Solving
8t = 7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7t' to each side of the equation.
8t + -7t = 7t + -7t

Combine like terms: 8t + -7t = 1t
1t = 7t + -7t

Combine like terms: 7t + -7t = 0
1t = 0

Divide each side by '1'.
t = 0

Simplifying
t = 0

See similar equations:

| (4z+5)(3-z)=0 | | 13x+24x-31x=144 | | 7y+2=6y-2 | | 3x^2-12x-180=0 | | 3y+8=2y-6 | | 2x^2-6x+14=0 | | 3x^7-243=0 | | 2x+10y+(-10y)+(-10x)= | | 193.6=m(10000)+b | | 2b-15=-25 | | -x=.63 | | 2.2(h-5.3)=0 | | 4x-7+16=3x+12 | | 8(1+4x)+7=207 | | 27x+9y+36z= | | 5x^2-26y-24=0 | | (5+y)(5y-3)=0 | | 3(4j+5)=2(-10+5) | | x-.15x=510000 | | r=-0.691 | | (1+s)+1= | | 5x+4y=500 | | y=kx+fx | | 0.18-0.03(x+2)=-0.03(2-x) | | 5x+2=6+9x | | (3y-9)(-2y^2+7y+1)= | | (3+5g)(2)= | | 4(g+4)=5(g-3) | | 2-4y+16=4 | | 4(9+5)=5(9-3) | | 3+6x=5x-4 | | -7x+10=90+x |

Equations solver categories